2017
DOI: 10.1093/cvr/cvw246
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion therapy with recombinant human relaxin-2 (Serelaxin) attenuates myocardial infarct size and NLRP3 inflammasome following ischemia/reperfusion injury via eNOS-dependent mechanism

Abstract: Serelaxin attenuates myocardial I/R injury and the subsequent caspase-1 activation via eNOS-dependent mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
71
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 40 publications
5
71
1
Order By: Relevance
“…Increasing evidences suggested that phosphorylation of eNOS, the target of Akt, was an important downstream effector in survival signaling in cardiomyocytes . Raleigh et al demonstrated that recombinant human relaxin‐2 (serelaxin) protects myocardium against I‐R injury by eNOS activation, while eNOS knock out abolished serelaxin's beneficial effects. Our results also showed that hydromorphine exhibited significant effect of increases in the levels of both p‐eNOS and NO in the isolated perfused heart following I/R injury compared with sham group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing evidences suggested that phosphorylation of eNOS, the target of Akt, was an important downstream effector in survival signaling in cardiomyocytes . Raleigh et al demonstrated that recombinant human relaxin‐2 (serelaxin) protects myocardium against I‐R injury by eNOS activation, while eNOS knock out abolished serelaxin's beneficial effects. Our results also showed that hydromorphine exhibited significant effect of increases in the levels of both p‐eNOS and NO in the isolated perfused heart following I/R injury compared with sham group.…”
Section: Discussionmentioning
confidence: 99%
“…28 Increasing evidences suggested that phosphorylation of eNOS, the target of Akt, was an important downstream effector in survival signaling in cardiomyocytes. [29][30][31] Raleigh et al 32 to myocardial injury by nitrative stress. 35,36 Thereby, these findings may on account of different disease models, type, and dose of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In the phase 3 RELAX‐AHF (Serelaxin, Recombinant Human Relaxin‐2, for Treatment of Acute Heart Failure) trial of patients with acute heart failure, those who received a 16‐hour infusion of serelaxin showed improvements in biomarker expression patterns reflecting cardiac, renal, and hepatic damage, and these improvements correlated with reductions in all‐cause mortality by day 180 39, 41. In animal models, serelaxin and other formulations of recombinant relaxin‐2 have been shown to be protective in experimental models of cardiac injury 15, 16, 17, 18, 42, 43…”
Section: Discussionmentioning
confidence: 99%
“…17,18) Notably, recent pilot clinical trials also suggested a protective role of RLX-2 for ischemic heart disease by indicating that RLX-2 administration was associated with increased myocardial salvage and improved ventricular remodeling. 19,20) These results suggested that RLX-2 may prove essential in the initial and progressing glucose metabolism dysfunction related CVDs.…”
mentioning
confidence: 84%